2000
DOI: 10.1159/000018307
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Histological and Immunopathological Features of 58 Patients with Subacute Cutaneous Lupus erythematosus

Abstract: Background: Subacute cutaneous lupus erythematosus (SCLE) is a distinct subset of cutaneous lupus erythematosus clinically characterized by psoriasiform and/or annular lesions and by a mild or absent systemic involvement. Objective: The Italian Group of Immunodermatology of the Italian Society of Dermatology and Venereology reviewed the cases of SCLE seen in 10 years (1987–1996). Patients: Forty-six women and 12 men have been retrospectively studied, 42% had annular lesions, 39% psoriasiform ones and 16% both.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 26 publications
2
48
0
4
Order By: Relevance
“…There are two morphologic variants of SCLE: annular and papulosquamous. A study of 58 SCLE patients found that 42% had annular SCLE and 39% exhibited papulosquamous SCLE, while 16% of patients showed features of both [18]. Other studies have found more papulosquamous SCLE [19] and [20].…”
Section: How Can We Differentiate the Cle Subtypes?mentioning
confidence: 99%
“…There are two morphologic variants of SCLE: annular and papulosquamous. A study of 58 SCLE patients found that 42% had annular SCLE and 39% exhibited papulosquamous SCLE, while 16% of patients showed features of both [18]. Other studies have found more papulosquamous SCLE [19] and [20].…”
Section: How Can We Differentiate the Cle Subtypes?mentioning
confidence: 99%
“…The most widely accepted classification of LE-specific cutaneous involvement includes acute CLE (ACLE) with its localized and generalized forms, subacute CLE (SCLE) with its annular and papulosquamous forms and chronic CLE (CCLE) including discoid LE (DLE), lupus panniculitis and chilblain lupus. Some authors postulated to separate an intermittent CLE (ICLE) group covering lupus tumidus, while others handle this subtype as a form of CCLE [8,9].…”
mentioning
confidence: 99%
“…Entre as manifestações clínicas, fotossensibilidade, alopecia, úlcera oral e fenômeno de Raynaud parecem sugerir pior prognóstico no lúpus cutâneo (16) . Outros estudos clínicos (6,17) sugerem que a sistematização do lúpus eritematoso cutâneo esteja associada com a extensão das lesões cutâneas, com a presença de fenômeno de Raynaud, úlceras orais, fotossensibilidade e positividade de anti-DNA. Estudo comparando marcadores de atividade lúpica em pacientes com LES e lúpus cutâneo (discóide ou subagudo) verificou que nefrite, artrite e títulos altos (≥1:320) de FAN estavam entre os fatores de risco para envolvimento sistêmico no lúpus (2) .…”
Section: Discussionunclassified
“…A pesquisa de autoanticorpos no soro de nossos pacientes mostrou diferença significante (p<0,04) dos anticorpos anti-DNA entre pacientes com LES (58,8%) e LECD (18,7% (17) . Anticorpo anti-Sm também tem sido considerado específico de LES, porém é detectado em apenas 30% dos casos (1) .…”
Section: Discussionunclassified